Dietary intake of fruits and beta-carotene is negatively associated with amyotrophic lateral sclerosis risk in Koreans: A case-control study. (April 2014) - Jin, Youri; Oh, Kiwook; Oh, Seong-il; Baek, Heejoon; Kim, Seung Hyun; Park, Yongsoon
<x content-type="archive" xml:space="preserve">Abstract</x> Objectives Amyotrophic lateral sclerosis (ALS), a rare progressive neurodegenerative disease, has been suggested to have an association with oxidative stress, and thus antioxidant dietary factors may influence pathophysiological mechanisms or the risk of ALS. The purpose of the present study was to investigate the hypothesis that intake of fruits, rich in antioxidant nutrients, is negatively associated with the risk of ALS. Methods Seventy-seven Koreans diagnosed with ALS according to the EI Escorial criteria-revised and the same number of age- and sex-matched healthy controls participated in this study. Dietary intake was estimated using the standardized food frequency questionnaire. Results Multivariate logistic regression analysis showed that fruit consumption was negatively associated with the risk of ALS, but intake of beef, fish, and fast food were positively associated with the risk of ALS. In addition, the risk of ALS was negatively associated with intake of plant calcium and beta-carotene, while positively associated with intake of total calcium and animal calcium. Intake of vegetables and other antioxidant nutrients had no effect on the risk of ALS in the present study. Discussion The intake of fruits and beta-carotene decreases the risk of sporadic ALS in this present study. However, large prospective and interventional studies are needed to confirm the effect of fruits and beta-carotene intake on the risk of ALS.